1992
DOI: 10.1177/016235329201600106
|View full text |Cite
|
Sign up to set email alerts
|

Gifted Secondary Students' Preferred Learning Style: Cooperative, Competitive, or Individualistic?

Abstract: The purpose of the paper is to consider the issue of cooperative learning for the gifted from the perspective of the gifted student's preferred learning style. The sample consisted of 169 intellectually bright/gifted senior high school students, 94 girls and 75 boys in Calgary. Their preferred learning style in respect to science, mathematics, and English was measured using the Learning Preference Scale-Students. Overall, the cooperative style was not significantly more preferred for any subject matter by boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 11 publications
0
34
0
3
Order By: Relevance
“…However, some researchers have found that cooperative learning may not be suitable for all students (Huber, Sorrentino, Davidson, Epplier, & Roth, 1992;Li & Adamson, 1992), especially gifted students. Li and Adamson (1992) conducted a study on the preferred learning styles of gifted secondary students that involved comparing the cooperative, competitive, and individualistic styles, and they found that the students performed better with the individualistic learning approach than with cooperative learning and that cooperative learning and achievement were not correlated.…”
Section: Classroom Work Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some researchers have found that cooperative learning may not be suitable for all students (Huber, Sorrentino, Davidson, Epplier, & Roth, 1992;Li & Adamson, 1992), especially gifted students. Li and Adamson (1992) conducted a study on the preferred learning styles of gifted secondary students that involved comparing the cooperative, competitive, and individualistic styles, and they found that the students performed better with the individualistic learning approach than with cooperative learning and that cooperative learning and achievement were not correlated.…”
Section: Classroom Work Stylesmentioning
confidence: 99%
“…Li and Adamson (1992) conducted a study on the preferred learning styles of gifted secondary students that involved comparing the cooperative, competitive, and individualistic styles, and they found that the students performed better with the individualistic learning approach than with cooperative learning and that cooperative learning and achievement were not correlated.…”
Section: Classroom Work Stylesmentioning
confidence: 99%
“…Although children in this study rated vignettes, which may or may not represent real-life experience, the results offer support for distinguishing between task-oriented and other-referenced competitive beliefs and behaviors (e.g., . Third, the gifted children studied by Li and Adamson (1992) tended to endorse competitive and individualistic learning styles over cooperative ones, suggesting that some degree of competitiveness might maximize the academic performance of gifted pupils. Rimm (1986) maintained that educators and parents should stress the importance of achievement without focusing exclusively on winning.…”
Section: Competition and Gifted Childrenmentioning
confidence: 96%
“…A s argued earlier, gifted children might prefer competitiveness in the classroom because they have fared well in previous competitive situations. Li and Adamson (1992) conducted a study to determine gifted high school seniors' preferred learning style in Science, Math, and English. Ninety-four girls and 75 boys completed the Learning Preference Scale for students, which asks about the preferences one has for a cooperative (e.g., "We get the work done faster if we all work together"), competitive (e.g., "Trying to be better than others makes me work well"), or individualistic (e.g., "I prefer to work by myself so I can go as fast as I like") learning experience.…”
Section: Competition and Gifted Childrenmentioning
confidence: 99%
“…Üstün yeteneklilerle yapılan çok az çalışma düşünme şekillerinin belirlenmesi ve geliştirilmesi ile ilgilidir (Kim vd., 2007). Var olan çalışmalar; öğrencilerin düşünme stilleri ya da şekilleri (Grigorenko & Sternberg,1997;Park, Park & Choe, 2005) ve öğrenme biçimlerini ya da stillerini (Chan, 2001;Li & Adamson, 1992;Oakland, Joyce, Horton & Glutting, 2000) tespit etmeye yönelik olarak yapılmıştır. Mevcut literatürde üstün yetenekli öğrencilerin düşünme yolları ve anlama şekillerinin geliştirilmesine yönelik çalışma yok denecek kadar azdır.…”
Section: Egs' Nin öğRetim Ilkeleri Etkileşim Prensibi Gereklilik Preunclassified